Exploring the cross-cultural communication challenges of foreign students in China: the mediating effects of social media interaction and psychological resilience - Xu, Min; bt. Shapii, Aspalila (Frontiers in Psychology, 2025)
With the development of international education, an increasing number of foreign students are choosing to study Chinese in China. However, due to cultural differences and adaptation challenges, enhancing these students’ Intercultural Communicative Competence (ICC) has become a pressing issue. Based on Self-Determination Theory (SDT), this study aims to explore how autonomy, competence, and relatedness influence the ICC of foreign students studying Chinese in China through the mediating effects of social media interaction and psychological resilience. A survey was conducted, collecting data from 500 valid samples of foreign students from various universities in China, encompassing diverse nationalities and cultural backgrounds. Structural equation modeling was employed to analyze the data. The findings reveal that autonomy, competence, and relatedness significantly and positively influence social media interaction and psychological resilience, which in turn enhance ICC. Competence emerged as the most influential factor, while psychological resilience played a critical role in cross-cultural adaptation. The results suggest that fostering autonomy, competence, and relatedness effectively enhances students’ ICC. This study provides theoretical support for the field of intercultural education and recommends that educational institutions leverage social media platforms and strategies to cultivate psychological resilience, helping students better adapt to multicultural environments.